AN ANALYSIS OF THE USE OF NOMINAL GROUP IN JAKARTA POST ONLINE NEWSPAPER ANALYSIS - Damayanti, Alfira; Iskandar, Iskandar (ELITERATE : Journal of English Linguistics and Literature Studies, 2023)
The researcher examined the nominal groups found in the Jakarta Post online newspapers in this study. A nominal group is a group of words that includes all additional information related to a noun (or a word that is the name of a person, place, or thing) as the main word. The goals of this study are to describe the different types of nominal groups that can be found in The Jakarta Post Online Newspapers. The Functional Grammar theory proposed by Linda Gerot and Peter Wignell (1994) was used by the researcher to cover six elements: “Thing, Deictic, Numerative, Epithet, Classifier, and Qualifier”. The data came from the Jakarta Post online newspaper, which was published from 17 July 2021, 2018 to 18 July 2021, 2018. The researcher investigated two articles. “The findings revealed 408 nominal groups identified in the Jakarta Post online newspaper as D is for Deictic, T is for Thing, Q is for Qualifier, C is for Classifier, E is for Epithet, N is for Numerative, with Data 1 (184 numbers), and Data 2 (184 numbers) (224 numbers)”